Refrigeration - Welch, T. (CIBSE knowledge series, 2008)
This publication is aimed at those entering the building services industry without previous knowledge of the subject, such as graduates with mechanical, electrical or civil engineering degrees. It will also be useful for anyone without specialist experience in refrigeration. Refrigeration is sometimes seen as a "black art" and something of a mystery, so this publication tries to unveil the workings and behaviour of refrigeration equipment applied into air conditioning for building services. --